Multi-agent modelling for simulation of customer-centric Supply Chain. (6th March 2007) - Labarthe, Olivier; Ferrarini, Alain; Espinasse, Bernard; Montreuil, Benoit
The analysis of coordination among the Supply Chain (SC) members is a key factor for improving its performance. The highly dynamic demand induced by the volatility of customers requires defining tools to improve the performance. This paper presents an agent-based modelling concept for simulation of customer-centric SC. We describe the specificities of such SCs at the enterprise modelling domain level and propose an approach permitting to explicitly take into account the customers and their behaviours. The approach uses three levels of modelling, successively leading to a domain model, a Conceptual Agent Model (CAM) and an Operational Agent Model (OAM). A case study from the personalised golf club industry illustrates the proposed approach.